Counseling services in Muslim communal life in Malaysia - Ismail, Zainab; Wan Ahmad, Wan Ibrahim; Ab. Rahman, Asyraf (IDOSI Publications, 2014)
Although counseling is a new concept for Muslim communal life in Malaysia, practically, it is actually an Islamic culture in regards to helping others.In addition, providing assistance to those in need has long been in existence in the early days of Islam.Counseling service has become part of support systems for married couples. Using a content analysis design, this article uses secondary materials as important sources of data. The data indicates that the counseling service has existed since the era of the Prophet Muhammad which was known as nasihah.During Saiyidina Umar al-Khattab’s era, he had established the so called Diwan al-Hisbah as the first step towards upgrading nasihah as a profession in regards to the missionary program and has been part of the approaches for missionary activities within the Islamic Religious Department of the country. The service among which include helping couples experiencing domestic conflict and providing necessary assistance to reestablish mutual understanding and strengthen their family ties and relations.